2007
DOI: 10.1002/adfm.200700289
|View full text |Cite
|
Sign up to set email alerts
|

Textured Tubular Nanoparticle Structures: Precursor‐Templated Synthesis of GaN Sub‐micrometer Sized Tubes

Abstract: Porous and sub‐micrometer tubes made of textured GaN nanoparticles have been synthesized by an in situ chemical reaction and characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and photoluminescence (PL) and Raman spectroscopies. The in situ reaction involves thermal decomposition and nitridation of 1D gallium oxyhydroxide (GaOOH) at temperatures in the range of 700–900 °C. The 1D shape of the precursor GaOOH is maintained in the resultant GaN t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…Herein, we report the fabrication of unique mesoporous quasi‐single‐crystalline Co 3 O 4 nanobelts by a thermal decomposition from precursory α ‐Co(OH) 2 nanobelts based on the topotactic relationship between the (0001) Co(OH) 2 and (111) Co 3 O 4 planes. During the formation of mesoporous quasi‐single‐crystalline Co 3 O 4 , the nanobelt frameworks (skeletons) could be maintained, as was expected based on previous work involving mesoporous quasi‐single‐crystalline Co 3 O 4 nanowires,26 our earlier research involving the fabrication of textured nanoparticle‐assembled GaN submicrotubes constructed from submicro‐sized GaOOH rods,27 and investigations involving [111]‐oriented growth of Co 3 O 4 from (0001) planes of β ‐Co(OH) 2 with layered brucite‐like structures 28. This topotactic growth will provide an effective and versatile route to controlled fabrication of nanostructured oxides with optimizable properties.…”
Section: Introductionsupporting
confidence: 57%
“…Herein, we report the fabrication of unique mesoporous quasi‐single‐crystalline Co 3 O 4 nanobelts by a thermal decomposition from precursory α ‐Co(OH) 2 nanobelts based on the topotactic relationship between the (0001) Co(OH) 2 and (111) Co 3 O 4 planes. During the formation of mesoporous quasi‐single‐crystalline Co 3 O 4 , the nanobelt frameworks (skeletons) could be maintained, as was expected based on previous work involving mesoporous quasi‐single‐crystalline Co 3 O 4 nanowires,26 our earlier research involving the fabrication of textured nanoparticle‐assembled GaN submicrotubes constructed from submicro‐sized GaOOH rods,27 and investigations involving [111]‐oriented growth of Co 3 O 4 from (0001) planes of β ‐Co(OH) 2 with layered brucite‐like structures 28. This topotactic growth will provide an effective and versatile route to controlled fabrication of nanostructured oxides with optimizable properties.…”
Section: Introductionsupporting
confidence: 57%
“…It is this topotactic feature that leads to the formation of single-crystalline ␤-NaYF 4 nanotubes at low hydrothermal temperature, rather than the dissolutionϪrenucleation processes described in the classical crystallization theories. 20,26,29,32 The multicolor fluorescence can be observed in the Yb 3ϩ /Er 3ϩ (green) and Yb 3ϩ / Tm 3ϩ (blue) co-doped ␤-NaYF 4 nanotubes synthesized from the hydrothermal in situ ion-exchange method. The visible and NIR upconversion luminescence spectra of ␤-NaYF 4 : 2% Er 3ϩ , 20% Yb 3ϩ and ␤-NaYF 4 : 2% Tm 3ϩ , 20% Yb 3ϩ under infrared excitation (978 nm) are shown in Figure 4a,b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The recent development of commercial blue-light emitters based on GaN has propelled these materials into the mainstream of interest. Up to now, many structures of GaN such as nanowires [2][3][4][5][6], nanorods [7][8][9][10][11], nanobelts [12], and tubes [13][14][15][16][17] have been successfully synthesized. Many reports showed that these one-dimensional (1D) structures of GaN have been grown by many methods, such as chemical vapor deposition [18], metal-organic chemical vapor deposition [19], molecular beam epitaxy [20], halide vapor-phase epitaxy [21], arc discharge [22], magnetron sputtering [23], chemical thermal-evaporation process [24], etching [25], and ammonolysis [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%